2008
DOI: 10.1146/annurev.neuro.31.060407.125639
|View full text |Cite
|
Sign up to set email alerts
|

Spike Timing–Dependent Plasticity: A Hebbian Learning Rule

Abstract: Spike timing-dependent plasticity (STDP) as a Hebbian synaptic learning rule has been demonstrated in various neural circuits over a wide spectrum of species, from insects to humans. The dependence of synaptic modification on the order of pre- and postsynaptic spiking within a critical window of tens of milliseconds has profound functional implications. Over the past decade, significant progress has been made in understanding the cellular mechanisms of STDP at both excitatory and inhibitory synapses and of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

38
1,287
0
6

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,636 publications
(1,331 citation statements)
references
References 165 publications
(218 reference statements)
38
1,287
0
6
Order By: Relevance
“…Extant literature holds that long-term potentiation (LTP) is a central mechanism underlying associative learning 186 . Recent research has focused on a form of LTP called spike timing-dependent plasticity (STDP) 187 . According to STDP, a modification in synaptic transmission occurs owing to variations in the timing of weak and strong synaptic inputs over tens of milliseconds.…”
Section: Box 3 | Neurobiology Of Learningmentioning
confidence: 99%
“…Extant literature holds that long-term potentiation (LTP) is a central mechanism underlying associative learning 186 . Recent research has focused on a form of LTP called spike timing-dependent plasticity (STDP) 187 . According to STDP, a modification in synaptic transmission occurs owing to variations in the timing of weak and strong synaptic inputs over tens of milliseconds.…”
Section: Box 3 | Neurobiology Of Learningmentioning
confidence: 99%
“…STDP is a learning rule which modifies the synaptic strength (weight) between two neurons as a function of the relative pre-and postsynaptic spike occurrence times [12]. Competitive learning takes the form of a winnertake-all (WTA) policy.…”
Section: Introductionmentioning
confidence: 99%
“…Hebb organized his ideas into three premises: (i) the first proposes that two neurons undergo metabolic and/or structural alterations when their activation patterns are correlated, for facilitation of transmission between these neurons; (ii) the second proposes that neurons that have correlated activities form a 'cell assembly' that have functional connection; (iii) the third presents a temporally concatenated activation of several cell assemblies, called 'phase sequence,' just as the flow of thought itself (Crick & Koch, 1990;Hebb, 1944Hebb, /2002. Since then, many experimental and theoretical studies have confirmed, revised, and expanded the largely theoretical and qualitative work performed by Hebb (Bliss & Lomo, 1973;Brown, Kairiss, & Keenan, 1990;Caporale & Dan, 2008;Crick & Koch, 1990;Kolb, 2003;Lechner & Byrne, 1998).…”
Section: More Recent Approaches In the Study Of Cognitionmentioning
confidence: 98%